The influence of pH on growth kinetics of yeasts in the presence of benzoate as a sole carbon source - Müncnerová, D; Augustín, J (Folia microbiologica, 1994)
The inhibitory effect and substrate properties of benzoic acid were estimated for 25 yeast strains belonging to genera Candida, Hansenula, Hypopichia, Rhodosporidium, Rhodotorula, Saitoella and Trichosporon. Benzoic acid can serve as a sole carbon source for growth of yeasts belong to genera Rhodotorula, Rhodosporidium and Saitoella in synthetic mineral media. Specific growth rate is strongly dependent both on the concentration of benzoate and the pH value of the cultivation media. Maximum specific growth rate on benzoate is observed in alkaline cultivation media at pH 7.0-7.5 whereas those for growth on glucose in mildly acidic media at pH 5.0. Some of the strains showed weak growth on benzoate even at pH 8.5. Some carotenoid-containing yeasts of the genera Rhodotorula and Rhodosporidium lost their ability to synthesize carotenoid pigments during growth in alkaline benzoate media.
Keywords: kinetika; uhlovodíky; kvasinky; uhlík; koncentrace vodíkových iontů; Biodegradation, Environmental; biodegradace; Hydrocarbons; Carbon; Models, Biological; Yeasts; Hydrogen-Ion Concentration; kyselina benzoová; Kinetics; kultivační média; biologické modely; Benzoates; Benzoic Acid; benzoáty; Culture Media